2021
DOI: 10.3389/fpsyg.2021.717959
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Inequalities in Mortality After Age 67: The Contribution of Psychological Factors

Abstract: Diverging trends of longer lives and increased inequalities in age-at-death invite to updated research on late-life mortality. Earlier studies have identified health behavior, childhood, psychosocial, and material conditions as key determinants of life expectancy, but the role of psychological factors remains a topic of debate. The current study is framed in a life course developmental perspective and assesses the mediating role of secondary control strategies (subjective age) and primary control capacity (per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…The effect sizes differed across studies between LR = 1.004 (Veenstra, Løset, & Daatland, 2021) and LR = 3.772 (Markides & Pappas, 1982). Significant effects in the expected direction (e.g., positive SPA or younger subjective age-predicted health/longevity) were reported in 79 studies (74%), whereas 28 studies (26%) reported no significant effects.…”
Section: Update Of Earlier Resultsmentioning
confidence: 89%
“…The effect sizes differed across studies between LR = 1.004 (Veenstra, Løset, & Daatland, 2021) and LR = 3.772 (Markides & Pappas, 1982). Significant effects in the expected direction (e.g., positive SPA or younger subjective age-predicted health/longevity) were reported in 79 studies (74%), whereas 28 studies (26%) reported no significant effects.…”
Section: Update Of Earlier Resultsmentioning
confidence: 89%
“…Perceived (agentic) control refers to the subjective appraisal of one’s ability to influence and predict outcomes and events across the life span (e.g., Heckhausen et al, 2010; Perry, 1991, 2003; Rothbaum et al, 1982; Skinner, 1996). Perceived control is a robust salutary predictor of overall well-being, objective and subjective health, and all-cause mortality across the life span (Chipperfield et al, 2012, 2019; Lachman & Weaver, 1998; Veenstra et al, 2021). In achievement settings, researchers have focused on the domain-specific construct of academic control, the perception of one’s ability to influence and predict their achievement outcomes.…”
Section: Student Debt: a Source Of Academic Disparitymentioning
confidence: 99%